2016
DOI: 10.15359/eys.21-50.4
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management development: the role of learning school on promotion of managers’ competence

Abstract: The aim of this study was to research the effects of using the Learning School to improve competency criteria of managers in Bank Saderat Iran and determine the effect of each criterion of this school. By using a Morgan table and assuming an unlimited population size, 384 individuals were randomly selected. After choosing six core competencies of the managers, data was collected using a 47-item questionnaire. After confirming the questionnaire's validity using SPSS and a Spearman's test, the significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Poorzaman, Yusefi, Soleimani, & Hemmatyar (2014), in a study entitled "The role of critical success on corporate entrepreneurship", concluded that cultural dimensions, developing a culture of learning and acquisition of skills is of key importance in order to promote knowledgebased companies, while the knowledge, skills and capacity of staff creativity affect their ability and capacity dimensions. Training, development and recruitment of the empowerment and implicating control aspects such as evaluation policies based on knowledge-based activities can be very effective (Poorzaman et al, 2014;Salamzadeh, Nejati & Salamzadeh, 2014, Salamzadeh, YousefNia, Radovic Markovic & Salamzadeh, 2016. Sepehrdoust and Shabkhaneh (2015), in a study entitled "Impact of knowledge-based components on organizational productivity", indicate that the four main variables of the knowledge-based economy; the education variable, information and communication technology innovations, economic incentives and regulations institutional are of greatest impact on growth and productivity of knowledge-based companies.…”
Section: Resultsmentioning
confidence: 99%
“…Poorzaman, Yusefi, Soleimani, & Hemmatyar (2014), in a study entitled "The role of critical success on corporate entrepreneurship", concluded that cultural dimensions, developing a culture of learning and acquisition of skills is of key importance in order to promote knowledgebased companies, while the knowledge, skills and capacity of staff creativity affect their ability and capacity dimensions. Training, development and recruitment of the empowerment and implicating control aspects such as evaluation policies based on knowledge-based activities can be very effective (Poorzaman et al, 2014;Salamzadeh, Nejati & Salamzadeh, 2014, Salamzadeh, YousefNia, Radovic Markovic & Salamzadeh, 2016. Sepehrdoust and Shabkhaneh (2015), in a study entitled "Impact of knowledge-based components on organizational productivity", indicate that the four main variables of the knowledge-based economy; the education variable, information and communication technology innovations, economic incentives and regulations institutional are of greatest impact on growth and productivity of knowledge-based companies.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the businesses are forced to develop and execute different strategies to attain superior business performances. The strategic decisions assist the managers to predict changes in the external business environment and the effective strategies enable them to access and use critical resources in order to attain competitive advantage (Salamzadeh et al, 2016). To be more specific, strategies on knowledge management are considered to have a positive impact on the performance of organizations and networks (Centobelli et al, 2018).…”
Section: Entrepreneur Networkingmentioning
confidence: 99%
“…This is because current and updated knowledge is critical for the success of any business. Thus, firms keep on striving for developing close relationships with other parties to minimize the uncertainties by mutually joining and increasing their resources' levels including knowledge resources as well (Salamzadeh et al, 2016).…”
Section: Entrepreneur Networkingmentioning
confidence: 99%
“…However, common business practices in the Czech Republic show that this is not always the case. Many companies do not incorporate business processes (or modify them) into their corporate strategy or into the generation of added value on a national and global scale [21], [6], [22]. Knowledge of the internal environment of a company is an essential requirement for its sustainability and prosperity, whilst adhering to the principle that the specific internal environment of a company is always unique, exceptional and original; the integrity of its constituent parts is enabled by its uniqueness.…”
Section: Literary Reserchmentioning
confidence: 99%